Commentary: Legal Education's Future; A Broader Horizon or a Narrowing Window? - Charles D. Kelso; R. Randall Kelso (Washington University Law Quarterly, 1981)
The curriculum and perspective of law schools today are broader than they have ever been, especially for students who elect to seek a broad legal education. Even broader legal education is not likely because factors both within and outside the universities point toward a narrowing of law school programs. There is at best an uneven case on the merits for further broadening of legal education.
Keywords: Law schools; Legal education; United States